Perkembangan Profitabilitas Dan Likuiditas Perusahaan E-Commerce Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023 - Ivanka, Dia; Haryati, Dini; Natalia, Nia (Politeknik Raflesia Press, 2024)
In terms of liquidity ratios, Sophee's overall financial performance experienced a significant decline. In terms of quick ratios, there was a decline from 209.3% in 2021 to 142.6% in 2023. Likewise, the current ratio decreased from 210.9% in 2021 to 144.1% in 2023. The cash ratio has also decreased, namely from 128.9% in 2021 to 34.41% in 2023. Toko Pedia's financial performance tends to decline but not too big and the ratio is still around 200% except for in 2023 where the cash ratio is 196.1%, down from 2021 of 253.4%. Bukalapak's financial performance in terms of quick ratio, current ratio and cash ratio is quite stable from 2021 to 2023 and is still around 200%. In terms of profitability ratios, Sophee's Gross Profit Margin has increased, although not too big, namely from 39.1% in 2021 to 44.7% in 2023. Likewise, Return On Sales which has a negative value for 2021 and 2022 has improved with a positive value of 3 .3% in 2023. Toko Pedia's financial performance, both in terms of Gross Profit margin and Return on sales, has not shown satisfactory results and tends to decline from 2021 to 2023. The same thing also happened to Bukalapak where the financial performance for the Gross Profit ratio Margin and Return on Sales show a decline from 2021 to 2023.